Careers in finance - Andrew Ellul; Marco Pagano; Annalisa Scognamiglio (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
The finance wage premium since the 1990s has arguably lured talent away from other industries. However, the allocation of talent is likely to respond to differences in career paths, not in wages at a given date. We use resume data to reconstruct the careers of 11,255 professionals in finance, high-tech and services from 1980 to 2017, and find that careers mostly develop within sectors. Careers in asset management feature higher and steeper pay profiles than those of employees in banking, insurance and non-finance, yet this career premium cannot be explained by higher risk. Labor market entry responds positively to career premia in asset management and high-tech, and these sectors are regarded as substitutes by potential entrants, consistently with high-tech competing with asset management in attracting talent.
Keywords: G20; G23; J24; J62; J63; 330; careers; finance premium; asset management; labor market entry; high-tech